Quercus ilex forests are influenced by annual variations in water table, soil water deficit and fine root loss caused by Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2013)
Itishypothesised thatmajor reductions intree vitality are related tomarked changes insoilwater content, extremely wet winters followed by dry summers, and the presence of pathogenic organisms which take advantage of this situation. This study helps clarify the role of annual variations in water table, soil water content and ﬁne root abundance in the decline of Quercus ilex forests, with special focus on trees growing in Phytophthora cinnamomi-infested soils. Conducted in western Spain, the study included 5 Q. ilex dehesa stands in which tree water status and soil water dynamic were compared in declining and non-declining trees, and 96 additional stands in which ﬁne root abundance and pathogen assessment were compared in declining and non-declining trees. Declining trees showed signiﬁcantly lower values than non-declining trees for leaf water potential and stomatal conductance. The period of waterlogging (2 months maximum, ﬂuctuating from −0.5 to −4.5m), the soil water content values observed in summer (signiﬁcantly higher in declining trees) and the similar presence of Pythium spiculum in declining and non-declining trees are not sufﬁcient in themselves to explain tree health status. However, ﬁne root density was 16.2% lower in declining than non-declining trees and 42% lower in P. cinnamomi-infected than non-infected trees. Root damage caused by P. cinnamomi in combination with periods of saturated soils favourable for the pathogen but unfavourable for the tree, coupled with small-scale differences in soil water-holding capacity, explain the symptoms and water status of declining trees. The combination of root damage and water stress explained above-ground symptoms of declining trees and will probably determine tree survival.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Oak decline; Open woodlands; Root density; Root-rot disease; Saturated soil; Water deﬁcit

Root system of Quercus suber L. seedlings in response to herbaceous competition and different watering and fertilisation regimes - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro; Madeira, Manuel (Agroforestry Systems, 2012)
Different management practices are commonly applied to increase pasture yield of Mediterranean open woodlands, but the consequences of increasing competition for soil resources with these practices on tree recruitment are still unknown. In a greenhouse study, belowground competition of Quercus suber L. seedlings growing together with natural (OakNP) or improved pasture (OakIP) was evaluated, and their root systems compared with those of seedlings growing in bare soil (OakBS). Two watering levels and two regimes of P2O5 fertilisation were also tested. Because of competition, the OakIP seedlings had their ﬁne root mass density, coarse root length, and shoot mass reduced by up to 40, 36, and 39%, respectively, when compared to OakNP seedlings. OakNP and OakBS seedlings showed similar average root density parameters and shoot mass values, indicating that Q. suber seedlings growing with natural pasture is a low competitive system. High availability of water and phosphorus did not mitigate the strength of competition between herbaceous plants and oak seedlings, and favoured the pasture to the detriment of the trees. Our ﬁndings suggest that P2O5 fertilisation and irrigation practices performed to improve herbaceous productivity will negatively inﬂuence recruitment of Q. suber seedlings.
Keywords: Cork oak; Dehesa; Improved pasture; Root density; Seedling recruitment

Quercus ilex root growth in response to heterogeneous conditions of soil bulk density and soil NH4-N content - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Soil and Tillage Research, 2009)
A greenhouse study examined the effects of heterogeneous conditions of soil bulk density and soil NH4-N content on the growth of holm oak (Quercus ilex L.) seedlings over an 8-month period. Heterogeneity of soil was produced inside 150 cm depth pots, by applying manual compaction or enriching different soil layers with NH4 (vertical heterogeneity) and, by splitting the root system into two columns with differing soil bulk density or NH4 conditions (horizontal heterogeneity). Root distribution patterns were assessed by collecting roots within layers, each 10 cm depth, and by recording both the ﬁne (diameter <2 mm) and the coarse (diameter 2 mm) root biomass. Root systems signiﬁcantly responded to the vertical gradients of soil bulk density, decreasing their maximum depth and showing lower values of ﬁne root densities at the layers with a dry bulk density of 1.62 Mg m3 . The split-root system showed that maximum rooting depth of the axis with a dry bulk density of 1.38 Mg m3 was limited by the reduced rooting depth of the adjacent more compacted axis. Root systems were less dense in the NH4 soil treatment than in the control soil treatment (34 mg dm3 vs. 212 mg dm3 ), even at the lowest rate used (0:1 g NH4 L 1 soil ). This high sensitivity to NH4 conducted to a signiﬁcant decrease of shoot height and root depth (50 and 43%, respectively). The split-root system showed that unfavourable conditions of NH4 content have local consequences on the rooting depth and systemic consequences on the ﬁne root density. The implications of root growth restrictions for Q. ilex natural regeneration, seedling survival, and decline are discussed.
Keywords: Oak decline; Quercus ilex; Root density; Root depth; Soil bulk density; Soil NH4 content

Quercus ilex root growth in response to heterogeneous conditions of soil bulk density and soil NH4-N content - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Soil and Tillage Research, 2009)
A greenhouse study examined the effects of heterogeneous conditions of soil bulk density and soil NH4-N content on the growth of holm oak (Quercus ilex L.) seedlings over an 8-month period. Heterogeneity of soil was produced inside 150 cm depth pots, by applying manual compaction or enriching different soil layers with NH4 (vertical heterogeneity) and, by splitting the root system into two columns with differing soil bulk density or NH4 conditions (horizontal heterogeneity). Root distribution patterns were assessed by collecting roots within layers, each 10 cm depth, and by recording both the ﬁne (diameter <2 mm) and the coarse (diameter 2 mm) root biomass. Root systems signiﬁcantly responded to the vertical gradients of soil bulk density, decreasing their maximum depth and showing lower values of ﬁne root densities at the layers with a dry bulk density of 1.62 Mg m3 . The split-root system showed that maximum rooting depth of the axis with a dry bulk density of 1.38 Mg m3 was limited by the reduced rooting depth of the adjacent more compacted axis. Root systems were less dense in the NH4 soil treatment than in the control soil treatment (34 mg dm3 vs. 212 mg dm3 ), even at the lowest rate used (0:1 g NH4 L 1 soil ). This high sensitivity to NH4 conducted to a signiﬁcant decrease of shoot height and root depth (50 and 43%, respectively). The split-root system showed that unfavourable conditions of NH4 content have local consequences on the rooting depth and systemic consequences on the ﬁne root density. The implications of root growth restrictions for Q. ilex natural regeneration, seedling survival, and decline are discussed.
Keywords: Oak decline; Quercus ilex; Root density; Root depth; Soil bulk density; Soil NH4 content